2017
DOI: 10.1016/j.gore.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Two sisters with Mayer-Rokitansky-Küster-Hauser syndrome and serous adenocarcinoma of the ovary

Abstract: BackgroundMayer-Rokitansky-Küster-Hauser syndrome is a rare entity with proposed genetic underpinnings. Ovarian carcinoma has well-described genetic associations and syndromes, although much of the etiology of the disease remains unknown.CasesTwo sisters present in the 1970s with primary amenorrhea, 46, XX karyotypes, and absent uteri consistent with MRKH syndrome. In the 2010s, both sisters again present for care. Case 1 presents one sister with stage IIIC serous ovarian adenocarcinoma and negative BRCA panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A literature review by Miao et al (2018) [5] , collected few case reports of Mullerian ducts anomalies with various types of ovarian neoplasms, the majority of which were found to be benign after histopathological evaluation. Huepenbecker et al (2017) [6] , reported a rare occurrence of ovarian cystadenocarcinoma in two sisters affected by MRKH syndrome with normal 46XY karyotype and negative ovarian cancer genetic panel screening. Also, Villa et al (2019) [7] , described a case of a 33-year-old patient with MRKH syndrome, ovarian low-grade serous carcinoma, and normal karyotype as well as negative screening for the breast cancer gene 1 and 2 (BRCA1/BRCA2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review by Miao et al (2018) [5] , collected few case reports of Mullerian ducts anomalies with various types of ovarian neoplasms, the majority of which were found to be benign after histopathological evaluation. Huepenbecker et al (2017) [6] , reported a rare occurrence of ovarian cystadenocarcinoma in two sisters affected by MRKH syndrome with normal 46XY karyotype and negative ovarian cancer genetic panel screening. Also, Villa et al (2019) [7] , described a case of a 33-year-old patient with MRKH syndrome, ovarian low-grade serous carcinoma, and normal karyotype as well as negative screening for the breast cancer gene 1 and 2 (BRCA1/BRCA2).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Mullerian dysgenesis syndrome have normal ovarian development. Few cases have been reported in the current literature about the development of uterine or ovarian tumors in patients with different classes of Mullerian dysgenesis but up to the authors’ best knowledge, there are no previous reports of ovarian tumor development in HWWS [5] , [6] , [7] . Thus, we report the first case of ovarian tumor development in HWWS.…”
Section: Introductionmentioning
confidence: 93%
“…Sertoli cellIIna(Tsaur et al, 1995)ChinaI4Germ cellImmature teratomaIII(Ghirardini and Magnani, 1995)ItalyI68EpithelialUndifferentiated carcinomaIIIIII(Takeuchi et al, 2006)Japanna8Germ cellYolk sac tumornaI(Mishina et al, 2007)Moldovana35Germ cellDysgerminomanaI(Kavallaris et al, 2011)GermanyII48EpithelialMixed epithelial carcinomaIIIIII(Bae et al, 2013)KoreaII31EpithelialSerous papillarycnaIII(Ko et al, 2012)KoreaII37EpithelialSerous carcinomaIIIIII(Nusrath et al, 2016)IndiaII65EpithelialEndometrioid carcinomanaI(Juusela et al, 2017)United StatesI72Sex-cord stromalBilat. Sex-cord stromal tumornaI(Huepenbecker et al, 2017)United Statesna64EpithelialSerous carcinomaIIIIIIna63EpithelialSerous tubal carcinomaIIIIIIPresent CaseItalyI33EpithelialBilat. Serous carcinomaIIIna, not available.aPrevious diagnosis of femur osteosarcoma at the age of 25, no chemotherapy or radiation therapy.bBorderline tumor of the other ovary.cSupernumerary ovary.…”
Section: Discussionmentioning
confidence: 99%
“…In only a few MRKHS cases the occurrence of gynecological cancer was reported. Of particular interest was the report of Huepenbecker et al describing two sisters affected with MRKHS, who also developed serous ovarian carcinoma ( Huepenbecker et al, 2017 ). This finding raised the possibility of a shared genetic origin of the two conditions, although data concerning the association of ovarian cancer with MRKHS are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The occurrence of a gynecological tumor was reported in only a few cases of MRKHS syndromes. 6 However, data on the association of a benign ovarian tumor are still limited. Authors report here a case of MRKH syndrome discovered during a laparotomy for a large ovarian tumor.…”
Section: Introductionmentioning
confidence: 99%